Ice sheet instability and meltwater events along the Svalbard–Barents Sea margin during the last 60,000 years - R.G. Lucchi; C. Caricchi; L. Sagnotti; M.E. Musco; G. Giorgetti; R. Ventrice; N. Douss; F. Princivalle; C. Morigi; P. Macrì; F.S. Gois Smith; A. Caburlotto; et al. (Global and Planetary Change, 2026)

Decoding Past Microbial Communities Shifts Induced by Natural and Anthropogenic Disturbance Events Through Extracellular DNA - S. Varrella; M. Tangherlini; C. Corinaldesi; L. Musco; A. Schirone; G. Armiento; R. Danovaro; A. Dell'Anno (Molecular Ecology, 2025)
Coastal marine ecosystems face escalating threats from multiple anthropogenic stressors, including the release of industrial contaminants. Despite decades of industrial activity impacting marine ecosystems, long‐term effects on microbial communities and related key ecological functions remain unclear. Here, we analysed the prokaryotic genetic signatures of extracellular DNA preserved in sediment layers dating from the mid‐17th century to the present day collected from two sites of one of the most polluted European coastal areas (i.e., Bagnoli‐Coroglio Bay, Tyrrhenian Sea), where industrial activities began in the early 20th century and ended in 1992. Archaeal 16S rDNA copy numbers were higher than bacterial ones, reaching values of 2.3 and 8.8 × 10 7 copies during pre‐industrial volcanic episodes and the intense industrial development period, respectively. Most of the archaeal genetic signatures identified along the sediment vertical profiles belong to Bathyarchaeia. The pre‐industrial period showed lower diversity in terms of Amplicon Sequence Variants (ASVs) belonging to 70 prokaryotic families when compared with industrialisation periods (182 families), suggesting prokaryotic ability to respond and change in relation to modified environmental conditions occurring over time. High microbial β‐diversity values were observed, with major shifts occurring for more than 50 prokaryotic taxa in both cores, suggesting that chemical contamination and volcanic eruptions fostered microbial succession, selecting certain taxa more adapted to cope with such adverse ecological conditions. Our findings indicate that extracellular DNA pools of marine sediments can hold information on long‐term changes in benthic microbial diversity, representing valuable archives for understanding ecosystem dynamics over time.

A Mediterranean record of Eulalia ornata (Annelida: Phyllodocidae) corroborating its fidelity link with the Sabellaria alveolata-reef habitat - E. SCHIMMENTI; L. MUSCO; S. LO BRUTTO; B. MIKAC; A. NYGREN; F. BADALAMENTI (Mediterranean Marine Science, 2015)
Among marine habitats Sabellaria alveolata-reefs deserve protection since they provide important ecosystem services and positive effects on biodiversity. Several marine species are listed among the S. alveolata-reef associated fauna, but characteristic species were seldom reported. Eulalia ornata (Annelida, Phyllodocidae) might represent an exception, since it appears common/abundant in S. alveolata-reefs of the Eastern Atlantic. The most evident geographical mismatch in the distributions of E. ornata and these biogenic reefs occurs in the Mediterranean Sea, where S. alveolata-reefs are commonly found, but E. ornata was never recorded, whilst E. viridis, a non-Mediterranean species, was previously listed among the dominant reef-associated taxa. The faunal characterization of the sabellarid reefs along the Sicily Channel revealed an Eulalia species as the dominant taxon associated with that habitat in the area. A taxonomic approach integrated with DNA barcoding, and comparisons with closely related species, allow us to report E. ornata as a new record for the Mediterranean Sea. We describe patterns of abundance and distribution and corroborate its status as a preferential species in the S. alveolata-reef habitat. Focusing on the biology and ecology of E. ornata could help us to better understand the dynamics and functioning of this valuable European shallow marine habitat.

Distribution patterns of shallow water polychaetes (Annelida) along the Alexandria coast, Egypt (eastern Mediterranean) - M. M. DORGHAM; R. HAMDY; H. H. EL RASHIDY; M. M. ATTA; L. MUSCO (Mediterranean Marine Science, 2014)
Shallow hard bottom and intertidal soft bottom polychaete assemblages of the Alexandria coast, southeastern Mediterranean (Levantine Sea), were studied during a complete annual cycle in order to analyze spatial temporal patterns of variation in assemblages, and relevant factors related to polychaete distribution. The present study recorded a total of 73 species, belonging to Syllidae (22 species), Nereididae (9 species), Serpulidae (6 species), Eunicidae (5 species) and other 19 families. The assemblages experienced pronounced spatial and temporal variation throughout the study area, but spatial variation appeared more important in determining the observed patterns. Polychaete distribution related to variation of grain size and sessile macrobenthos cover suggesting that these structural variables accounted more than the physical-chemical ones (namely BOD, dissolved oxygen, organic carbon, organic matter, salinity, temperature, pH) in influencing the patterns of assemblages’ distribution. The present study is the southeastern-most one dealing with ecology and distribution patterns of hard bottom polychaetes from the Mediterranean Sea, as well as one of the few studies dealing with intertidal soft bottom polychaetes in the Levant Basin.

Concern about the spread of the invader seaweed Caulerpa taxifolia var. distichophylla (Chlorophyta: Caulerpales) towards the West Mediterranean - L. MUSCO; F. ANDALORO; B. MIKAC; S. MIRTO; T. VEGA FERNADEZ; F. BADALAMENTI (Mediterranean Marine Science, 2014)
The new Australian alien seaweed Caulerpa taxifolia var. distichophylla, after being established along the Turkish Mediterranean coast in 2006, was recorded in Southern Sicily in 2007. Since then local fishermen claimed support to counteract the effects of entanglement of large amounts of the alien strain wrack in their trammel nets, causing the gear to become ineffective. The further northward and westward spread of the new alien strain is supposed to be limited by winter temperature. We present novel data confirming that the new alien strain is fully naturalized in Central Mediterranean and is expanding its range beyond such limit (i.e. the 15°C February isotherm), thus becoming potentially able to colonize the western basin. By means of a preliminary estimation of effects on native polychaete assemblages, and considering some peculiarities of Sicily (mostly linked to its geographical position in the Mediterranean Sea), the risk linked to the increasing range of distribution of the invasive algae is highlighted.

Shift in Sabella spallanzanii (Polychaeta, Sabellidae) spawning period in the Central Mediterranean Sea: a consequence of climate change? - A. GIANGRANDE; M. LICCIANO; L. MUSCO; L. STABILI (Mediterranean Marine Science, 2010)
Sabella spallanzanii is a large tubicolous filter feeder polychaete common in the Mediterranean fouling assemblages where it plays an important role in structuring the community. Its reproductive biology is well known and had been investigated since 1993. During the past few years a shift in its reproductive period has been observed. In 2008 the presence of ripe eggs in the females was observed at least two months in advance compared to the past. This was confirmed during the 2009 when spawning and fertilization were observed three months in advance compared to the past. Possible causes of this shift may be related to the increasing surface temperature in the Central Mediterranean Sea.

Reproduction activity of Exogone naidina (Polychaeta: Exogoninae) in a population from the Apulian coast (Adriatic Sea) - M. Gherardi; M. Mastrodonato; L. Sion; L. Musco; E. Lepore; M. Sciscioli; A. Giangrande (Marine Biology, 2005)

Polychaete assemblages along a rocky shore on the South Adriatic coast (Mediterranean Sea): patterns of spatial distribution - A. Giangrande; A. L. Delos; S. Fraschetti; L. Musco; M. Licciano; A. Terlizzi (Marine Biology, 2003)